Killer of enemies - Bruchac, Joseph, 1942- (Bruchac, Joseph, 1942- Killer of enemies, 2013)
"In a world that has barely survived an apocalypse that leaves it with pre-twentieth century technology, Lozen is a monster hunter for four tyrants who are holding her family hostage"--